Study protocol for feasibility and safety of adopting early oral feeding in post total laparoscopic total gastrectomy (overlap esophagojejunostomy): A multicentre randomized controlled trial - Yang, Jun; Yang, Qinchuan; Wang, Weidong; Chai, Xiaoyan; Zhou, Haikun; Yue, Chao; Gao, Ruiqi; Mo, Zhenchang; Ji, Panpan; Dong, Danhong; Wei, Jiangpeng; Liu, Jinqiang; et al. (Frontiers in Nutrition, 2022)
Background: Total laparoscopic total gastrectomy (TLTG) for gastric cancer, especially with overlap esophagojejunostomy, has been verified that it has advantages of minimally invasion, less intraoperative bleeding, and faster recovery. Meanwhile, early oral feeding (EOF) after the operation has been demonstrated to significantly promote early rehabilitation in patients, particularly with distal gastrectomy. However, due to the limited application of TLTG, there is few related research proving whether it is credible or safe to adopt EOF after TLTG (overlap esophagojejunostomy). So, it is urgent to start a prospective, multicenter, randomized clinical trials to supply high level evidence. Methods/Design: This study is a prospective, multicentre, randomized controlled trial with 200 patients (100 in each group). These eligible participants are randomly allocated into two different groups, including EOF group and delay oral feeding (DOF) group after TLTG (overlap esophagojejunostomy). Anastomotic leakage will be carefully observed and recorded as the primary endpoints; the period of the first defecation and exhaust, postoperative length of stay and hospitalization expenses will be recorded as secondary endpoints to ascertain the feasibility and safety of adopting EOF after TLTG (overlap esophagojejunostomy). Discussion: Recently, the adoption of TLTG was limited due to its difficult anastomotic procedure, especially in vivo esophagojejunostomy. With the innovation and improvement of operating techniques, overlap esophagojejunostomy with linear staplers simplified the anastomotic steps and reduced operational difficulties after TLTG. Meanwhile, EOF had received increasing attention from surgical clinicians as a nutrition part of enhanced recovery after surgery, which had shown better results in patients after distal gastrectomy. Considering the above factors, we implemented EOF protocol to evaluate the feasibility and safety of adopting EOF after TLTG (overlap esophagojejunostomy), which provided additional evidence for the development of clinical nutrition guidelines. Trial Registration: This study was approved by the Chinese Ethics Committee of Registering Clinical Trials (ChiECRCT20200440) and registered on Chinese Clinical Trials Registry (ChiCTR2000040692). Keywords: total laparoscopic total gastrectomy, overlap esophagojejunostomy, early oral feeding, delay oral feeding, oral nutritional supplements, oral nutritional supplements